Pengaruh Pelaksanaan.Pembelajaran.Kewirausahaan.dan Efikasi.Diri Terhadap.Kesiapan.Berwirausaha.Siswa.Kelas.XII.di SMKN 1 Lubuk Basung - Nia Patri Ciana; Elvi Rahmi (Jurnal Ecogen, 2020)
This study. aims to reveal.the effect of the implementation of entrepreneurship learning and self-efficacy on entrepreneurial readiness students. This type of research is associative descriptive. The study population is all students of class XII at vocational high school 1 Lubuk Basung. The sampling technique used was proportional to random sampling, and the technique obtained 75 students as samples. The data collection technique used was a questionnaire. This study uses multiple regression analysis. The results of this study indicate that: (1) the. Implementation of entrepreneurial learning has a significant influence on the readiness..of..entrepreneurial grade XII students at vocational high school 1 Lubuk Basung; (2) self-efficacy has a significant influence on entrepreneurial readiness of class XII students at vocational high school 1 Lubuk Basung; (3) the implementation of entrepreneurship learning and self-efficacy together have a significant effect of 63.2% on..the readiness..of entrepreneurship..in class XII..students..at vocational high school 1 Lubuk Basung.Keywords : entrepreneurship learning, self-efficacy, entrepreneurship readiness